Mosquitoes' larval habitat characteristics and Aedes aegypti resistance status to malathion in Jember - Nihayah, Husnatun; Purwatiningsih, Purwatiningsih; Utami, Eva Tyas; Fajariyah, Susantin; Lelono, Asmoro; Puspitasari, Reni; Rohmah, Hidayatur (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2025)
Water-holding containers serve as breeding sites for Aedes aegypti. The control of mosquito breeding sites and the use of household insecticides are some of the DHF control methods. The use of household insecticides over a long period can reduce the susceptibility of mosquitoes to these insecticides. This research aims to determine the mosquito's habitat characteristics and to determine the Aedes aegypti resistance status to malathion in Jember.  A total of 61 houses were surveyed, and the various types of containers encountered at the sampling locations were recorded. Larvae and pupae found at the sampling location are brought and hatched in the laboratory. Aedes aegypti was tested for resistance status to malathion insecticide using a CDC bottle bioassay and biochemical nonspecific esterase enzyme activity. A total of 140 containers were found in this study, and 36.43% of them are Aedes aegypti larvae/pupae habitat. Types of containers used as mosquito larval habitat are bottles/glasses, bathtubs, used basins/buckets, water storage buckets, trash cans, refrigerator water containers, used cans, gutters, livestock drinking water containers, fish ponds, plant pots, used livestock cages, used toilets, used jugs, used animal feeders, and used aquariums. The mortality of Aedes aegypti reached 42.3% (resistant). Meanwhile, the results of biochemical tests showed an increase in the activity of the nonspecific esterase enzyme. This study concludes that Aedes aegypti from Jember has been resistant to malathion insecticide